Identifikasi Potensi Wisata di Desa Kutai Lama - Setiawan, Fajar; Tohari, Amin (TAFANI: Jurnal Pengabdian Masyarakat, 2023)
This research examines the identification of tourism potential in Kutai Lama village. This research aims to reveal how to identify and develop tourism potential in Kutai Lama Village. The research methods used are observation, interviews and documentation. The sample for this research was tourists from Kutai Lama village. The data obtained was analyzed using a qualitative approach. The results of this research show that Kutai Lama tourism has great potential to be developed in both the natural, religious and cultural tourism sectors. However, its development is still lacking as in the natural tourism sector. Therefore, a tourism plan was created which aims to develop and promote natural tourism.